PERTUMBUHAN BEBERAPA JENIS SEMAI LEGUM PADA TANAH ULTISOL DI POLYBAG - YosHariyantho, Dwi; Wardah, Wardah; Umar, Husain; Taiyeb, Asgar (Jurnal Warta Rimba, 2021)
Ultisols are mineral soils that develop from old parent materials and have undergone further weathering. Constraints to the utilization of ultisol soils have low organic matter content, acidic soil reactions, low base saturation, high Al content and have a clay to sandy clay texture. Therefore, to reforest it, it is necessary to look for tree legumes that are adapted to grow in these soil conditions. The purpose of this study was to determine the growth of several species of legume seedlings on ultisol soil in polybags. This research was conducted for three months, from November 2020 to January 2021, located in the BPDASHL Permanent Nursery in Palu-Poso, Palu, Central Sulawesi. This study used a completely randomized design (CRD) method with four treatments and ten replications, so that there were 40 experimental units. The treatments were applicated, namely: L1 = Sengon (Paraserianthes falctaria (L.) Nielsen); L2 = Acacia (Acacia mangium Willd); L3 = Johar (Senna siamea Lamk); L4 = Turi (Sesbania grandiflora L). The parameters observed in this study were seedling height, diameter, number of leaves, value of stem stiffness and number of root nodules. The result of study showed that legume seedlings had different growth responses on ultisol soil in polybags. The Sengon (Paraserianthes falctaria (L.) Nielsen) legume species had higher height, diameter, leaf number, seedling firmness and number of noduoles compared to (L4) Turi (Sesbania grandiflora L), (L3) Johar (Senna siamea Lamk), (L2) Acacia (Acacia mangium Willd) legumes.Keywords: Legume tree, ultisol soil